Assessment Manajemen Sekuriti PT AQUA - Edy Soesanto; Vina Hariyati; Munisari Munisari; Navia Naveli (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
Information technology (IT) has been used by PT Tirta Investama (AQUA) Pandaan to support its business and operational activities. On a limited basis, this utilization is directly overseen by the Danone Information Systems (DAN'IS) division. All information technology provision and development for all Danone firms is handled by a sizable subsidiary called DAN'TS. On February 1st of this year, it was found that Danone already operates 20 different mineral water businesses throughout Indonesia. So it means that, this type of company is one of the biggest for now. Exchange of information is a natural part of every company activity. Information security is the protection of information technology equipment, both computer and non-computer from all threats and threats from outsiders. This makes information security indirectly guarantee business protection, reduce various risks that occur, and reduce investment returns.